Pengaruh Keterwakilan Perempuan Dalam Pembentukan Peraturan Daerah Provinsi Sumatera Barat - Helmi Chandra; Hendriko Arizal (Fakultas Hukum, Universitas Warmadewa, 2022)
In West Sumatra in the 2019 Election, the West Sumatra Provincial DPRD has experienced a decline. The weak position of women in the legislative body will certainly make it difficult for women to fight for women's rights and not produce regional regulations that are discriminatory against women. It is hoped that women's activities in the policy-making process will be able to produce a number of changes in each policy. However, the tendency is that there is still a lack of women's DPRDs to exercise their right of initiative in drafting regional regulations, placement of positions that are not strategic and the existence of resistance hindering the role of women DPRD members to be able to form regional regulations.